Successful live birth in a Chinese woman with P450 oxidoreductase deficiency through frozen-thawed embryo transfer: a case report with review of the literature - Ping Pan; Lingyan Zheng; Xiaoli Chen; Jia Huang; Dongzi Yang; Yu Li (BMC, 2021)
Abstract Background Congenital adrenal hyperplasia (CAH) caused by P450 oxidoreductase deficiency (PORD) in 46, XX patients is characterized by genital ambiguity, primary amenorrhea, absent or incomplete sexual maturation, infertility, skeletal malformations and so on. But few pregnancies have been reported from these female patients with PORD. Case description A 29-year-old Chinese woman with PORD due to the compound heterozygous mutation (c.1370G > A/c.1196_1204del) in the P450 oxidoreductase (POR) gene had suffered from primary amenorrhea and infertility. She had one cancelled cycle of ovulation induction due to low serum estradiol(E2), high progesterone(P) levels and thin endometrium, then in vitro fertilization (IVF) was recommended. At the first IVF cycle, 4 oocytes were retrieved and 4 viable embryos were cryopreserved due to thin endometrium associated with low E2 and prematurely elevated P after ovarian stimulation, even though oral dexamethasone were used to control adrenal P overproduction at the same time. When basal P fell to < 1.5 ng/ml after the therapy of oral dexamethasone, artificial endometrial preparation and frozen embryo transfer were performed, resulting in a twin pregnancy. She delivered a healthy boy and a healthy girl by caesarean section at 37 weeks and 2 days of gestation. After the literature search in PORD women, no spontaneous pregnancy has been reported and only two previous case reports of 3 successful pregnancies through IVF were summarized. Conclusions It is the third report that successful pregnancy was achieved in a CAH woman caused by a compound heterozygous POR mutation, with primary amenorrhea and disorders of steroidogenesis. It seemed that disorders of steroidogenesis caused by PORD didn't impair the developmental potential of oocytes. IVF and frozen embryo transfer after adequate hormonal control and endometrial preparation should be an effective infertility treatment for PORD women.